2006
DOI: 10.1016/j.exer.2005.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced exacerbation of retinal degeneration in a rat model of Smith–Lemli–Opitz syndrome

Abstract: Potentiation of retinal degeneration by intense light exposure, and its amelioration by an antioxidant, were studied in a rat model of Smith-Lemli-Opitz syndrome (SLOS), in comparison with normal (control) Sprague-Dawley rats. The SLOS model is created by treating rats with AY9944, a selective inhibitor of cholesterol synthesis at the level of 3β-hydroxysterol-Δ 7 -reductase. A subset of rats was treated with dimethylthiourea (DMTU), a synthetic antioxidant, 24 and 1 hr prior to light exposure. Half of the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 50 publications
(55 reference statements)
2
36
0
Order By: Relevance
“…Photoreceptor outer segment membranes are highly enriched in PUFA (32). We have shown recently (18,19) that: a) the SLOS rat model is more susceptible to intense light-induced retinal degeneration than normal albino rats; b) the histologic damage correlates with levels of lipid peroxides; c) ERG deficits and levels of lipid peroxides in retinas of SLOS rats under normal ambient lighting conditions are comparable to those in retinas of light-damaged (but otherwise normal) albino rats; and d) pretreatment of rats with a free radical scavenger (dimethylthiourea) affords substantial protection from light-induced retinal damage in both normal albino and SLOS rats. In fact, lipid peroxidation has been linked to retinal photodamage by other investigators (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photoreceptor outer segment membranes are highly enriched in PUFA (32). We have shown recently (18,19) that: a) the SLOS rat model is more susceptible to intense light-induced retinal degeneration than normal albino rats; b) the histologic damage correlates with levels of lipid peroxides; c) ERG deficits and levels of lipid peroxides in retinas of SLOS rats under normal ambient lighting conditions are comparable to those in retinas of light-damaged (but otherwise normal) albino rats; and d) pretreatment of rats with a free radical scavenger (dimethylthiourea) affords substantial protection from light-induced retinal damage in both normal albino and SLOS rats. In fact, lipid peroxidation has been linked to retinal photodamage by other investigators (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The methods used for histologic and quantitative morphometric analysis of retinas were as described in detail previously (11,18).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a cholesterolderived oxysterol that is structurally analogous to compound 10 has been reported to be present in ozone-exposed lung lavage and in a human bronchial epithelial cell line, and this oxysterol appears to be toxic at micromolar concentrations ( 69 ). Light has been reported to exacerbate retina degeneration in a rat model of SLOS and this observation could well be due to accelerated free radical oxidation of 7-DHC ( 22,70 ). In addition, the formation and accumulation of 7-DHC oxysterols might be modifi ed by enzymatic transformations, and therefore different tissues may show specifi c 7-DHC-derived oxysterol profi les.…”
Section: Discussionmentioning
confidence: 99%
“…This was necessary in order to be able to characterize the onset and progression of the biochemical, morphological, and electrophysiological features of the retinal degeneration that occurs in this model, since the rodent retina undergoes substantial development over the fi rst several weeks of postnatal life ( 41,42 ). It has been demonstrated that the levels of lipid hydroperoxides in retinas of AY9944-treated rats are comparable to those found in photo-damaged retinas of control rats, and that exposure of AY9944-treated rats to intense visible light greatly accelerates the formation and steady-state accumulation of such oxidized lipids in the retina, which correlates with markedly increased severity and geographic extent of the associated retinal degeneration in this model ( 43,44 ).…”
Section: Isolation Of Oxysterols From Brain Tissues Of Ay9944-treatedmentioning
confidence: 97%